(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
This article is about the current state of sports medicine and physical therapy. The article also mentions the formation of sports medicine in the historical context. You will find a detailed description of the practical application and action of sports medicine and physical therapy in this article.